Analysis of the Hydraulic Jump Characteristics in a Stilling Basin to Avoid Dam Failure - Eldina Fatimah; Azmeri Azmeri; Qurratul 'Aini; Muhammad Fauzi; Maimun Rizalihadi (International Journal of Disaster Management, 2023)
Flooding may occur due to dam failure at downstream of the spillway. Stilling basin of the spillway plays an important role in reducing turbulence generated by hydraulic jumps. It can avoid flooding and local scouring as well. Therefore, this study aims to analyze hydraulic jump characteristics experimentally. Two series of structures namely initial (S0) and final (S1) were tested. The S0 model is the United States Bureau of Reclamation (USBR) III type, while S1 is set the adverse slope of 1:2 at the downstream and lowering the bottom elevation of the channel by 4 m. Measurements were taken on the length of hydraulic jumps, water level and high speed before-after hydraulic jumps at various return periods discharges (Q) of 2, 5, 10, 25, 50, 100 and 1000 years. It is found that at S1, the jump is submerged, causing the relative hydraulic jump height (y2-y1)/y1 to be 40-90% higher than S0. Furthermore, the compression of more than 50% of the hydraulic jump length ratio (Lj/y2) was indicated at S1. In addition, the energy dissipation efficiency (εt) obtained for each discharge at S1 ranged from 58-84% (good absorption). On the other hand, at S0, the εt produced was around 70-89% (Q2-Q50) and 45% (Q100 and Q1000). It can be concluded that the modification of USBR III can reduce the vulnerability of the bottom and downstream parts of the stilling basin. It is expected that the potential flood disaster due to the stilling basin failure of the dam can be eliminated. These results may be used as recommendation to the disaster management strategies, such as improving dam safety guidelines, informing emergency response plans, or guiding infrastructure design to withstand hydraulic forces.